Co‐exposure of cadmium and lead on bone health in a southwestern Chinese population aged 40‐75 years. Issue 3 (3rd November 2019) - Li, Xiaomeng; Li, Renjia; Yan, Jiuming; Song, Yang; Huo, Jiao; Lan, Zhen; Chen, Jinyao; Zhang, Lishi
Abstract: Both cadmium (Cd) and lead (Pb) are associated with bone health, but studies exploring the effects of Cd and Pb co‐exposure on bone health are rare. This study aimed to assess the interactive effects of Cd and Pb co‐exposure on bone health. In total, 799 participants, living in the targeted areas (located in southwestern China) for more than 15 years, aged 40‐75 years, and subsisted on homegrown rice and vegetables were investigated. Cd and Pb levels in urine and blood samples, as well as bone mineral density, T ‐ and Z ‐score were determined. After being adjusted for covariates, the T ‐score was negatively correlated with blood Pb in men ( P < .05); for women and non‐smoking women, the T ‐score was negatively correlated with urinary Pb ( P < .05). Moreover, after being adjusted for covariates, the Z ‐score was negatively correlated with urinary Pb in non‐smoking women ( P < .05). No positive association of prevalence of osteoporosis with Cd and Pb exposure was found. However, at an additive scale, positive interactions of urinary Cd and Pb on the prevalence of osteoporosis for women and non‐smoking women, and the same interactions to blood Cd and Pb for men were found. There was also a positive interaction of urinary Cd and Pb for women at a multiplicative scale. This study suggests Cd and Pb exposure could exert detrimental effects on bone health, with possible underlying interactions. Nevertheless, more studies are needed to explore the interactive effects of heavy metal co‐exposure. Abstract : Interactive effects of cadmium (Cd) and lead (Pb) co‐exposure on bone health were assessed. At additive scale, positive interactions of urinary Cd and Pb on the prevalence of osteoporosis for women and non‐smoking women, and the same interaction to blood Cd and Pb for men were found. There was also a positive interaction of urinary Cd and Pb for women at a multiplicative scale. This study suggests Cd and Pb exposure could exert detrimental effects on bone health, with possible underlying interactions.